Prognosis of patients with hepatocellular carcinoma treated with immunotherapy: development and validation of the CRAFITY score - Scheiner, Bernhard; Pomej, Katharina; Kirstein, Martha M.; Hucke, Florian; Finkelmeier, Fabian; Waidmann, Oliver; Himmelsbach, Vera; Schulze, Kornelius; von Felden, Johann; Fründt, Thorben W.; Stadler, Marc; Heinzl, Harald; et al. (Journal of hepatology, 2022)
Background & Aims - Immunotherapy with atezolizumab plus bevacizumab represents the new standard of care in systemic front-line treatment of hepatocellular carcinoma (HCC). However, biomarkers that predict treatment success and survival remain an unmet need. - Methods - Patients with HCC put on PD-(L)1-based immunotherapy were included in a training set (n = 190; 6 European centers) and a validation set (n = 102; 8 European centers). We investigated the prognostic value of baseline variables on overall survival using a Cox model in the training set and developed the easily applicable CRAFITY (CRP and AFP in ImmunoTherapY) score. The score was validated in the independent, external cohort, and evaluated in a cohort of patients treated with sorafenib (n = 204). - Results - Baseline serum alpha-fetoprotein ≥100 ng/ml (hazard ratio [HR] 1.7; p = 0.007) and C-reactive protein ≥1 mg/dl (HR, 1.7; p = 0.007) were identified as independent prognostic factors in multivariable analysis and were used to develop the CRAFITY score. Patients who fulfilled no criterion (0 points; CRAFITY-low) had the longest median overall survival (27.6 (95% CI 19.5-35.8) months), followed by those fulfilling 1 criterion (1 point; CRAFITY-intermediate; 11.3 (95% CI 8.0-14.6) months), and patients meeting both criteria (2 points; CRAFITY-high; 6.4 (95% CI 4.8-8.1) months; p <0.001). Additionally, best radiological response (complete response/partial response/stable disease/progressive disease) was significantly better in patients with lower CRAFITY score (CRAFITY-low: 9%/20%/52%/20% vs. CRAFITY-intermediate: 3%/25%/36%/36% vs. CRAFITY-high: 2%/15%/22%/61%; p = 0.003). These results were confirmed in the independent validation set and in different subgroups, including Child-Pugh A and B, performance status 0 and ≥1, and first-line and later lines. In the sorafenib cohort, CRAFITY was associated with survival, but not radiological response. - Conclusions - The CRAFITY score is associated with survival and radiological response in patients receiving PD-(L)1 immunotherapy. The score may help with patient counseling but requires prospective validation. - Lay summary - The immunotherapy-based regimen of atezolizumab plus bevacizumab represents the new standard of care in systemic first-line therapy of hepatocellular carcinoma (HCC). Biomarkers to predict treatment outcome are an unmet need in patients undergoing immunotherapy for HCC. We developed and externally validated a score that predicts outcome in patients with HCC undergoing immunotherapy with immune checkpoint blockers.